IMPLEMENTASI KEBIJAKAN KARTU JAKARTA PINTAR (KJP) PLUS PADA JENJANG PENDIDIKAN SEKOLAH DASAR (SD) DI KECAMATAN TANAH ABANG JAKARTA PUSAT - Ulfia Fitria Ningsih (2023)
The implementation of the KJP Plus policy at the elementary school level in Tanah Abang District, Central Jakarta has a number of problems, so it can be interpreted that its implementation has not been optimal. The purpose of this study was to analyze how the KJP Plus policy was implemented at the elementary school level in Tanah Abang District, Central Jakarta from the point of view of the Grindle and Right to Education policy implementation model. The method used in this study is a qualitative research method with a descriptive research design and data analysis with an inductive approach. The author tries to understand the object of research by using existing theory, and associated and developed with the data that has been obtained to become a hypothesis. Grindle's policy implementation model has two important variables that can determine the success and failure of a policy implementation, including (1) Policy Content and (2) Implementation Environment. The final results of the study show that the degree of change expected from the KJP Plus policy has not been achieved because there are still obstacles, especially in the distribution of KJP Plus, so it is necessary to evaluate and understand the policy by implementers, in this case the school needs to be involved to collect data and verify more continue (check and balance) the data of prospective KJP Plus recipients. Another problem is supervision that is less than optimal for KJP Plus recipients so that there is still misuse of funds. The implementation of KJP Plus in relation to fulfilling the Right to Education shows that the Provincial Government of DKI Jakarta has supported and guaranteed the implementation of the 12 Year Compulsory Education Program for the people of DKI Jakarta.